Triada obrazów akwatycznych jako podstawa integralności kompozycji filmu dokumentalnego Ołeksandra Awszarowa i Switłany Rudiuk Wasz Wasyl - Mychajłowa, Tetiana (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article is dedicated to analysing the compositional integrity of Oleksandr Avsharov and Svitlana Rudyuk’s documentary Yours, Vasyl (2019) through the prism of key aquatic images, including the city flood from the archival materials of Kyiv from 1970, dirty water from the poet’s sister’s dreams and the flood, stream and sea from Stus’s poetry (Ще до жнив не дожив..., Із циклу «Забуттям», Костомаров у Саратові). On the basis of these aquatic images, represented by key textual messages, the plot of the film is schematically arranged in a triad, which in turn plays the role of a graphic image of a mountain – a symbol of the poet’s steadfastness and victory. Attention is also drawn to the rich symbolism of the images, the skillful intertwining of the visual and auditory, the past and the present, thanks to which the image of the Stus seems alive and modern, which is what the filmmakers wanted to achieve.